Conductive silver paste, preparation method and application thereof

By adding solid-contained regulator and silver powder in the preparation process of conductive silver paste, and performing multiple homogenized dispersion and physical elimination treatments, the problem of difficult to take into account both high solids and good dispersion is solved, and the good dispersion and conductivity of conductive silver paste under high solids content is achieved.

CN119153169BActive Publication Date: 2025-04-15ENOVATE3D (HANGZHOU) TECH DEV CO LTD

Patent Information

Application Number
CN202411645469.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-15
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing conductive silver paste is difficult to take into account both high solid content and good dispersion, resulting in problems such as needle plugging, uneven discharge during printing, and holes and cracks after curing.

Method used

A preparation method is adopted, including mixing the epoxy resin, a curing agent, a first solvent and a second solvent, adding a solid regulator and homogenizing dispersion, then adding silver powder and performing a second homogenizing dispersion, and finally removing the solid regulator by physical elimination treatment to obtain a conductive silver paste.

Benefits of technology

The conductive silver paste has good dispersion under high solid content, can be completely cured at a lower temperature and has good conductivity. After curing, it is dense and full, and has no holes or cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153169B_ABST
    Figure CN119153169B_ABST
Patent Text Reader

Abstract

The present invention provides a conductive silver paste, a preparation method and application thereof. The preparation method comprises: mixing an epoxy resin, a curing agent, a first solvent and a second solvent, adding a solid content regulator after obtaining an organic phase, dispersing to obtain a modified organic phase and adding silver powder, dispersing to obtain a coarse mixed silver paste and performing a physical elimination treatment to remove the solid content regulator to obtain a conductive silver paste; the viscosity of the epoxy resin is ≤1000mPa·s, the solid content regulator comprises one or more of esters and ketones with a saturated vapor pressure of 3~100mmHg@20℃, and the silver powder comprises spherical silver powder and flaky silver powder. The present invention improves the dispersion uniformity of the silver paste through a two-step solid content regulation method, so that the silver paste can be completely cured at a lower temperature and still have a certain conductivity, and is dense and substantial after curing, and has no holes or cracks in morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic industry, and in particular to a conductive silver paste, a preparation method and application thereof. Background Art

[0002] With the rapid development of the electronics industry, the demand for various portable electronic devices (such as membrane switches, circuit boards, sensors and solar cells, etc.) is increasing day by day. Conductive silver paste has excellent conductivity and oxidation resistance, and can be used to manufacture integrated circuits, solar cells, film thickness resistors and other electronic components. It has been widely used in wiring, connection and packaging in the microelectronics industry.

[0003] The process of filling holes in printed circuit boards using metal 3D printing has become increasingly mature. The market has higher and higher requirements for hole filling technology, the application scenarios are becoming more and more complex and varied, and the requirements for silver paste performance are also increasing. Generally, the higher the silver powder content in the silver paste, the better its conductivity, and it is not easy to have holes after the hole filling and curing. However, the dispersibility of silver powder in the organic phase is limited. The higher the silver powder content, the more difficult it is to disperse the silver powder, and it is easy to agglomerate, causing silver paste to block the needle during printing. In addition, the curing temperature of the silver paste has a great influence on the morphology of the hole filling. High temperature (above 150°C) will cause hole deformation and silver paste extrusion.

[0004] After the low-solid silver paste is filled and solidified, a large number of cracks and voids will be generated inside the holes as the solvent evaporates. Therefore, it is necessary to increase the solid content of silver powder as much as possible and reduce the solvent content in the silver paste. However, as the silver powder content increases, the dispersibility of the silver powder will be greatly reduced using the traditional pulping process (silver powder is added to the organic phase, homogenized and dispersed, and three-roller dispersion), resulting in uneven dispersion and serious agglomeration, which ultimately manifests as needle blockage in printing and uneven discharge of silver paste. In addition, in order to prevent the substrate from being deformed and the silver paste in the hole from being squeezed out due to heating and curing, the silver paste is also required to be completely cured at a lower temperature (such as 80~150℃) and still have a certain conductivity.

[0005] Patent CN 113096848 A discloses a preparation process and application of a 140°C low-temperature curing silver paste, which uses an iodine-containing alcohol solution to pretreat the silver powder, and selects and matches high and low boiling point solvents with good compatibility with epoxy resin to improve the uniformity of the silver powder in the silver paste. However, the maximum solid content of the silver paste prepared by this method is only 60%, and the degree of curing shrinkage of the silver paste is large, which will cause a large number of cracks and voids in the pores after curing; and when the dried, non-agglomerated silver powder is pretreated with an alcohol solution, the risk of the silver powder itself agglomerating and difficult to disperse is greatly increased. Summary of the invention

[0006] The main purpose of the present invention is to provide a conductive silver paste, a preparation method and application thereof, so as to solve the problem that the conductive silver paste in the prior art cannot have both high solid content and good dispersibility.

[0007] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided a method for preparing a conductive silver paste, comprising the following steps: step S1, mixing an epoxy resin, a curing agent, a first solvent and a second solvent to obtain an organic phase; step S2, adding a solid-containing regulating agent to the organic phase, and performing a first slurry dispersion to obtain a modified organic phase; step S3, adding silver powder to the modified organic phase, and performing a second slurry dispersion to obtain a coarse mixed silver paste; step S4, performing a physical elimination treatment on the coarse mixed silver paste to remove the solid-containing regulating agent to obtain a conductive silver paste; wherein the viscosity of the epoxy resin is ≤1000mPa·s, the solid-containing regulating agent comprises one or more of esters and ketones with a saturated vapor pressure of 3~100mmHg@20℃, and the silver powder comprises spherical silver powder and flaky silver powder.

[0008] Further, in step S2, the solid-containing regulating agent includes one or more of ethyl acetate, propylene glycol methyl ether acetate, n-propyl acetate, sec-butyl acetate, methyl 2-methoxypropionate, tert-butyl propionate, butyl acetate, cyclohexanone, 3,3-dimethoxy-2-butanone, cyclopentanone, 2-hexanone and methyl isobutyl ketone; and / or the weight percentage of the solid-containing regulating agent in the coarse mixed silver paste is 2-10%.

[0009] Further, the D50 of the spherical silver powder is 100 nm~2 μm; and / or the D50 of the flaky silver powder is 3~20 μm; and / or the weight ratio of the spherical silver powder to the flaky silver powder is 1:(0.33~3).

[0010] Furthermore, the solid content of the coarsely mixed silver paste is 80-85%, and the solid content of the conductive silver paste is 87-92%.

[0011] Further, in step S4, the physical elimination treatment method includes one or more of vacuum homogenization, heating evaporation, vacuum rotary evaporation and vacuum drying; the number of cycles of vacuum homogenization is 2 to 8 times, the vacuum degree of a single cycle is 2 to 10 kPa, the rotation speed is 1000 to 2000 rpm, and the time is 3 to 10 min; and / or the temperature of heating evaporation is 50 to 80°C, and the time is 30 to 90 min; and / or the vacuum degree of vacuum rotary evaporation is 50 to 150 Pa, the rotation speed is 80 to 120 rpm, the temperature is 40 to 80°C, and the time is 20 to 60 min; and / or the vacuum degree of vacuum drying is 0.05 to 0.1 atm, the temperature is 40 to 80°C, and the time is 30 to 90 min.

[0012] Furthermore, the weight percentage of the solid-content regulating agent in the coarse mixed silver paste is 3-6%, the physical elimination treatment method is vacuum homogenization, the number of cycles of vacuum homogenization is 3-5 times, the vacuum degree of a single cycle is 3-6 kPa, the rotation speed is 1200-1800 rpm, and the time is 3-5 min.

[0013] Furthermore, in step S1, the first solvent is one or more of an ester solvent or a ketone solvent with a boiling point of 180-300°C, and the second solvent is one or more of an organic solvent with a boiling point of 60-160°C; the volume ratio of the first solvent to the second solvent is 1:(0.5-1.5).

[0014] Further, the first solvent includes one or more of DBE, ethylene glycol diacetate, alcohol ester dodecahydrate, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, di-tert-butyl malonate, ethyl succinate, isophorone, 1,3-cyclohexanedione, 4-ethylcyclohexanone and 1,2-cyclohexanedione; the second solvent includes one or more of ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, allyl butyl ether, 1,1,3,3-tetramethoxy-1,3-dimethyldisiloxane, ethylene glycol ethyl ether, propylene glycol dimethyl ether, ethylene glycol dimethyl ether, N,N-dimethylformamide, 1-methyl-3-pyrrolidone, N-methylpyrrole and 1,1-dimethoxy-N,N-dimethylethylamine.

[0015] Further, in step S1, the epoxy resin includes one or more of bisphenol F epoxy resin F170, alicyclic epoxy resin CY179 and alicyclic epoxy resin of Jiangsu Taitel, and the alicyclic epoxy resin of Jiangsu Taitel includes one or more of TTA21, TTA26, TTA15, TTA16 and TTA28, wherein the weight percentage of bisphenol F epoxy resin F170 in the epoxy resin is ≤30%; and / or the weight percentage of epoxy resin in the organic phase is 60-90%; and / or the curing agent includes a cationic epoxy resin curing agent, and the cationic epoxy resin curing agent includes one or more of CTI100, CTI80A, CTI80P, CTI101A, CTI80B and CTI300 of Changzhou Gaojing; and / or the weight ratio of epoxy resin to curing agent is 100:(0.5-1.5).

[0016] Furthermore, step S1 also includes the step of adding a dispersing aid during the mixing process; the dispersing aid includes one or more of the following substances: AKN01, AKN210, AKN7010, AKN2140 of Foshan Qianyou, KMT-J4201, MKT-8866, KMT-3026 of Foshan Corning, BYK180, BYK111, BYK410 of BYK Chemical; and / or the weight percentage of the dispersing aid in the conductive silver paste is 0.2~1%.

[0017] Furthermore, the rotation speed of the first homogenization dispersion is 1500-2500 rpm, and the time is 3-10 min; and / or the rotation speed of the second homogenization dispersion is 500-1000 rpm, and the time is 3-15 min.

[0018] Further, the silver powder is divided into three parts, namely the first silver powder, the second silver powder and the third silver powder; the first silver powder is first added to the organic phase and homogenized at 500-1000 rpm for 1-5 min; then the second silver powder is added and homogenized at 500-1000 rpm for 1-5 min; finally, the third silver powder is added and homogenized at 500-1000 rpm for 1-5 min to obtain a coarse mixed silver slurry.

[0019] Further, step S4 includes the following steps: step S41, subjecting the coarse mixed silver paste to a first freezing homogenization and roller dispersion in sequence to obtain a first fine mixed silver paste, wherein the temperature of the first freezing homogenization is -15~0°C; step S42, subjecting the first fine mixed silver paste to a physical elimination treatment to obtain a second fine mixed silver paste; step S43, subjecting the second fine mixed silver paste to a second freezing homogenization to obtain a conductive silver paste, wherein the temperature of the second freezing homogenization is -15~0°C.

[0020] Furthermore, independently, the number of cycles of the first frozen homogenate and the second frozen homogenate is 2 to 10 times, and a single cycle includes the first sub-frozen homogenate and the second sub-frozen homogenate performed in sequence, the rotation speed of the first sub-frozen homogenate is 1000 to 2000 rpm, and the time is 2 to 10 min; the rotation speed of the second sub-frozen homogenate is 300 to 600 rpm, and the time is 2 to 10 min.

[0021] According to one aspect of the present invention, a conductive silver paste is provided, which is obtained by the above-mentioned preparation method of the present invention. The conductive silver paste is used for printing with a line width of 500 μm and below. During the continuous 24-hour discharge process of the conductive silver paste, the flow fluctuation is less than 10%.

[0022] According to one aspect of the present invention, a curved printed circuit board is provided. The curved printed circuit board is obtained by filling holes with the conductive silver paste of the present invention. The resistance of the filled holes of the curved printed circuit board is ≤0.1Ω, and the conductivity of the curved printed circuit board is ≥95%.

[0023] By applying the technical solution of the present invention, a coarse mixed silver paste with a low silver powder solid content is first prepared to make the silver powder fully and evenly dispersed in the organic phase, and then the excess volatile solid content regulator in the silver paste is removed by physical elimination treatment, so as to increase the silver powder solid content in the silver paste. The present invention uses esters and ketones with specific saturated vapor pressure as solid content regulators, which can be conveniently removed by physical elimination while adjusting the solid content of the silver paste, so that the prepared conductive silver paste still has good dispersibility at high solid content. The present invention improves the dispersion uniformity of the silver paste through a two-step solid content regulation method, so that the silver paste can be completely cured at a lower temperature and still have a certain conductivity, and is dense and full after curing, and has no holes or cracks in morphology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A state diagram of the silver paste according to Example 1 of the present invention is shown;

[0025] Figure 2 The morphology of the silver paste after hole filling and curing according to Example 1 of the present invention is shown;

[0026] Figure 3 shows a state diagram of the silver paste according to Example 5 of the present invention;

[0027] Figure 4 The morphology of the silver paste after hole filling and curing according to Example 5 of the present invention is shown;

[0028] Figure 5 A state diagram of the silver paste according to Example 8 of the present invention is shown;

[0029] Figure 6 The morphology of the silver paste after hole filling and curing according to Example 8 of the present invention is shown;

[0030] Figure 7 shows a state diagram of the silver paste according to Example 11 of the present invention;

[0031] Figure 8 The morphology of the silver paste after hole filling and curing according to Example 11 of the present invention is shown;

[0032] Fig. 9 A state diagram of the silver paste according to Comparative Example 1 is shown;

[0033] Fig.10 The figure shows the morphology of the silver paste hole filling after curing according to Comparative Example 1;

[0034] Fig.11 The morphology of the silver paste hole filling after curing according to Comparative Example 2 is shown;

[0035] Fig.12 A state diagram of the silver paste according to Comparative Example 4 is shown;

[0036] Fig.13The morphology of the silver paste hole filling after curing according to Comparative Example 4 is shown;

[0037] Fig.14 A state diagram of the silver paste according to Comparative Example 6 is shown;

[0038] Fig.15 The morphology of the silver paste hole filling after curing according to Comparative Example 6 is shown;

[0039] Fig.16 A state diagram of the silver paste according to Comparative Example 7 is shown;

[0040] Fig.17 The morphology of the silver paste hole filling after curing according to Comparative Example 7 is shown. DETAILED DESCRIPTION

[0041] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0042] As described in the background of the present invention, there is a problem in the prior art that the conductive silver paste cannot take into account both high solid content and good dispersibility. In order to solve the above problem, in a typical embodiment of the present invention, a method for preparing a conductive silver paste is provided, comprising the following steps: step S1, mixing an epoxy resin, a curing agent, a first solvent and a second solvent to obtain an organic phase; step S2, adding a solid content regulator to the organic phase, and performing a first slurry dispersion to obtain a modified organic phase; step S3, adding silver powder to the modified organic phase, and performing a second slurry dispersion to obtain a coarse mixed silver paste; step S4, performing a physical elimination treatment on the coarse mixed silver paste to remove the solid content regulator to obtain a conductive silver paste; wherein the viscosity of the epoxy resin is ≤1000mPa·s, the solid content regulator includes one or more of esters and ketones with a saturated vapor pressure of 3~100mmHg@20℃, and the silver powder includes spherical silver powder and flaky silver powder.

[0043] The present invention first mixes epoxy resin, curing agent, first solvent and second solvent to obtain an organic phase. Subsequently, a solid-containing regulator is added to the organic phase, and a first homogenization dispersion is performed to obtain a modified organic phase, wherein the solid-containing regulator includes one or more of esters and ketones with a saturated vapor pressure of 3~100mmHg@20℃. The inventor unexpectedly found during the research process that when the prepared conductive silver paste is used to fill the through-holes of a curved printed circuit board during 3D printing, the curved substrate will be slightly deformed due to heating and curing, and the low-viscosity epoxy resin will be fully infiltrated with the holes, so that it can be quickly cured at low temperatures, and even if it is subjected to stress caused by deformation of the substrate, it will not be squeezed out as a whole. When the viscosity is too high, the resin cures slowly, and the resin is not completely cured after the substrate is deformed by heat, resulting in a large amount of silver paste in the holes of the substrate being squeezed out, affecting the filling effect. Therefore, the use of a low-viscosity epoxy resin in the present invention is more conducive to achieving low-temperature rapid curing of the silver paste and improving the morphology after filling and curing.

[0044] The inventors found during the research process that if the saturated vapor pressure of the solid content regulator is too low, it will be difficult to remove by physical elimination due to low volatility, and it will be difficult to increase the solid content of the final silver paste. If the saturated vapor pressure of the solid content regulator is too high, it will evaporate too quickly during the physical elimination process due to its strong volatility, and the solid content regulator in the local area of ​​the silver paste will be extracted too quickly and too much, resulting in silver powder agglomeration, poor discharge performance, and poor conductivity in the silver paste. Therefore, the present invention uses esters and ketones with the above-mentioned saturated vapor pressure as solid content regulators, which can be easily removed by physical elimination while adjusting the solid content of the silver paste, so that the prepared conductive silver paste still has good dispersibility at high solid content.

[0045] Then, silver powder is added to the modified organic phase, and a second homogenization dispersion is performed to obtain a coarse mixed silver paste, wherein the silver powder includes spherical silver powder and flaky silver powder. If only spherical silver powder is used, there are fewer conductive paths between the silver particles after curing, and it is impossible to conduct electricity; if only flaky silver powder is used, the density of the silver flakes is small, the stacking is loose, and the conductivity is poor. Therefore, the present invention adopts a mixture of spherical silver powder and flaky silver powder, which can well solve the above-mentioned problems existing in the use of single-morphology silver powder, and is conducive to the formation of silver paste with compact silver powder stacking, excellent conductivity, and excellent discharge performance. Finally, the coarse mixed silver paste is physically eliminated to remove excess volatile solid content regulators in the silver paste to obtain a conductive silver paste.

[0046] The present invention first prepares a coarse mixed silver paste with low silver powder solid content, so that the silver powder is fully and evenly dispersed in the organic phase, and then removes the excess volatile solid content regulator in the silver paste by physical elimination treatment, so as to increase the silver powder solid content in the silver paste. Since the silver paste is already fully and evenly dispersed in a relatively dilute state, the removal of the solid content regulator at this time has little effect on the evenly dispersed silver powder. Compared with the directly prepared high solid content silver paste, the two-step solid content regulation method of the present invention can improve the dispersion uniformity of the silver paste, so that the silver paste can be completely cured at a lower temperature and still have a certain conductivity. After curing, it is dense and full, with no holes or cracks in the morphology, and can further avoid the silver paste from being squeezed out after heating and curing, and can be used for filling holes in curved panels and printed circuit boards with poor high temperature resistance.

[0047] In a preferred embodiment, in step S2, the solid content regulator includes one or more of ethyl acetate, propylene glycol methyl ether acetate, n-propyl acetate, sec-butyl acetate, methyl 2-methoxypropionate, tert-butyl propionate, butyl acetate, cyclohexanone, 3,3-dimethoxy-2-butanone, cyclopentanone, 2-hexanone and methyl isobutyl ketone; and / or the weight percentage of the solid content regulator in the coarse mixed silver paste is 2-10%. The above-mentioned solid content regulator has better compatibility with epoxy resin and silver powder, and has a more suitable saturated vapor pressure, which can better dissolve the raw materials while being conveniently removed by physical elimination, thereby further improving the dispersibility while increasing the solid content of the silver paste.

[0048] In order to further improve the stacking performance, conductivity and discharge performance of the silver paste, in a preferred embodiment, the D50 of the spherical silver powder is 100nm~2μm; and / or the D50 of the flaky silver powder is 3~20μm; and / or the weight ratio of the spherical silver powder to the flaky silver powder is 1:(0.33~3). After the spherical silver powder is solidified, there are fewer conductive paths between the silver particles, the density of the flaky silver powder is small, and the stacking is loose, which is not conducive to improving the conductivity. Therefore, the present invention uses a mixture of spherical silver powder and flaky silver powder, which is conducive to achieving the best match between conductivity and discharge performance.

[0049] As described above, the present invention first prepares a coarse mixed silver paste with a low silver powder solid content, so that the silver powder is fully and evenly dispersed in the organic phase, and then removes excess volatile solid content regulators in the silver paste by physical elimination treatment, so as to increase the silver powder solid content in the silver paste. Specifically, in a preferred embodiment, the solid content of the coarse mixed silver paste is 80-85%, and the solid content of the conductive silver paste is 87-92%.

[0050] In a preferred embodiment, in step S4, the physical elimination treatment method includes one or more of vacuum homogenization, heating evaporation, vacuum rotary evaporation and vacuum drying, all of which can fully remove the solid content regulator while avoiding affecting the remaining components, which is beneficial to improving the solid content and dispersion performance of the silver paste.

[0051] Specifically, the parameters of the physical elimination treatment are preferably adapted to the type and content of the solid-containing regulating agent. For example, by adopting an appropriate extraction speed, the phenomenon of uneven dispersion and agglomeration of silver powder caused by excessive extraction of the solid-containing regulating agent in local areas of the silver paste can be better reduced; by adopting an appropriate number of cycles or treatment time, the problem of poor dispersion of the silver paste caused by severe heating inside the silver paste or even local solidification can be better reduced.

[0052] Specifically, the number of cycles of vacuum homogenization is 2 to 8 times, the vacuum degree of a single cycle is 2 to 10 kPa, the rotation speed is 1000 to 2000 rpm, and the time is 3 to 10 min; and / or the temperature of heating evaporation is 50 to 80 ° C, and the time is 30 to 90 min; and / or the vacuum degree of vacuum rotary evaporation is 50 to 150 Pa, the rotation speed is 80 to 120 rpm, the temperature is 40 to 80 ° C, and the time is 20 to 60 min; and / or the vacuum degree of vacuum drying is 0.05 to 0.1 atm, the temperature is 40 to 80 ° C, and the time is 30 to 90 min. Under the above conditions, the solid-containing regulator can be fully removed to increase the solid content of the silver paste while further improving the dispersibility of the silver paste. It should be noted that the specific parameters such as the number of cycles and the processing time can be adaptively adjusted according to the type and content of the solid-containing regulator to achieve the removal of the solid-containing regulator. These are understandable to those skilled in the art and will not be repeated here.

[0053] Based on the above reasons, it is most preferred that, in a preferred embodiment, the weight percentage of the solid content regulating agent in the coarse mixed silver paste is 3~6%, the physical elimination treatment method is vacuum homogenization, the number of cycles of vacuum homogenization is 3~5 times, the vacuum degree of a single cycle is 3~6kPa, the rotation speed is 1200~1800rpm, and the time is 3~5min. The above conditions can achieve the optimal effect of increasing the solid content of silver paste and improving the dispersibility of silver paste.

[0054] In a preferred embodiment, in step S1, the first solvent is one or more of an ester solvent or a ketone solvent with a boiling point of 180-300°C, and the second solvent is one or more of an organic solvent with a boiling point of 60-160°C; the volume ratio of the first solvent to the second solvent is 1:(0.5-1.5). Under the above conditions, the best matching of the organic phase solvent can be achieved, which is more conducive to the full dissolution of the silver powder and the further improvement of the dispersibility of the silver paste.

[0055] Based on similar reasons, it is further preferred that in a preferred embodiment, the first solvent includes one or more of DBE, ethylene glycol diacetate, alcohol ester dodecahydrate, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, di-tert-butyl malonate, ethyl succinate, isophorone, 1,3-cyclohexanedione, 4-ethylcyclohexanone and 1,2-cyclohexanedione; the second solvent includes one or more of ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, allyl butyl ether, 1,1,3,3-tetramethoxy-1,3-dimethyldisiloxane, ethylene glycol ethyl ether, propylene glycol dimethyl ether, ethylene glycol dimethyl ether, N,N-dimethylformamide, 1-methyl-3-pyrrolidone, N-methylpyrrole and 1,1-dimethoxy-N,N-dimethylethylamine.

[0056] The type of low-viscosity epoxy resin can be selected from conventional materials as needed. In a preferred embodiment, in step S1, the epoxy resin includes one or more of bisphenol F epoxy resin F170, alicyclic epoxy resin CY179 and alicyclic epoxy resin from Jiangsu Taitel, and the alicyclic epoxy resin from Jiangsu Taitel includes one or more of TTA21, TTA26, TTA15, TTA16 and TTA28, wherein the weight percentage of bisphenol F epoxy resin F170 in the epoxy resin is ≤30%; and / or the weight percentage of epoxy resin in the organic phase is 60-90%; and / or the curing agent includes a cationic epoxy resin curing agent, and the cationic epoxy resin curing agent includes one or more of CTI100, CTI80A, CTI80P, CTI101A, CTI80B and CTI300 from Changzhou Gaojing; and / or the weight ratio of epoxy resin to curing agent is 100:(0.5-1.5). The viscosity of the epoxy resin is more compatible with the silver paste system of the present invention, and the molecular weight is relatively small, which is conducive to better low-temperature curing of the silver paste and further improving the morphology of the silver paste after curing.

[0057] In a preferred embodiment, step S1 further includes the step of adding a dispersing aid during the mixing process; the dispersing aid includes one or more of the following substances: AKN01, AKN210, AKN7010, AKN2140 of Foshan Qianyou, KMT-J4201, MKT-8866, KMT-3026 of Foshan Corning, BYK180, BYK111, BYK410 of BYK Chemical; and / or the weight percentage of the dispersing aid in the conductive silver paste is 0.2-1%. The above conditions are more conducive to assisting the full curing of the silver paste at low temperature and further improving the dispersibility.

[0058] Based on similar reasons, in a preferred embodiment, the rotation speed of the first homogenate dispersion is 1500-2500 rpm, and the time is 3-10 min; and / or the rotation speed of the second homogenate dispersion is 500-1000 rpm, and the time is 3-15 min.

[0059] In order to further improve the mixing and dispersion effect of the silver powder, in a preferred embodiment, the silver powder is divided into three parts, namely, the first silver powder, the second silver powder and the third silver powder; the first silver powder is first added to the organic phase and homogenized at 500-1000 rpm for 1-5 min; then the second silver powder is added and homogenized at 500-1000 rpm for 1-5 min; finally, the third silver powder is added and homogenized at 500-1000 rpm for 1-5 min to obtain a coarse mixed silver slurry.

[0060] In a preferred embodiment, step S4 includes the following steps: step S41, subjecting the coarse mixed silver paste to a first freezing homogenization and roller dispersion in sequence to obtain a first fine mixed silver paste, wherein the temperature of the first freezing homogenization is -15 to 0°C; step S42, subjecting the first fine mixed silver paste to a physical elimination treatment to obtain a second fine mixed silver paste; step S43, subjecting the second fine mixed silver paste to a second freezing homogenization to obtain a conductive silver paste, wherein the temperature of the second freezing homogenization is -15 to 0°C. The silver powder particles can be further uniformed by multiple freezing homogenization and roller dispersion, thereby further improving the dispersion uniformity of the silver paste. Preferably, roller dispersion is performed in a three-roller machine, wherein the spacing of the three-roller machine is 80μm / 40μm, 40μm / 20μm, and 20μm / 10μm, respectively.

[0061] Based on similar reasons, in a preferred embodiment, the first frozen homogenate and the second frozen homogenate are cycled 2 to 10 times, respectively and independently, and a single cycle includes the first sub-frozen homogenate and the second sub-frozen homogenate performed sequentially, the rotation speed of the first sub-frozen homogenate is 1000 to 2000 rpm, and the time is 2 to 10 min; the rotation speed of the second sub-frozen homogenate is 300 to 600 rpm, and the time is 2 to 10 min.

[0062] According to one aspect of the present invention, a conductive silver paste is provided, which is obtained by the above-mentioned preparation method of the present invention. The conductive silver paste is used for printing with a line width of 500 μm or less, and the flow fluctuation of the conductive silver paste during the continuous 24-hour discharge process is less than 10%. It can take into account both high solid content and good dispersibility, can be completely cured at a lower temperature and still have a certain conductivity, and is dense and full after curing, and has no holes or cracks in morphology.

[0063] According to one aspect of the present invention, a curved printed circuit board is provided. The curved printed circuit board is obtained by filling holes with the above-mentioned conductive silver paste of the present invention. The resistance of the filled holes of the curved printed circuit board is ≤0.1Ω, and the conductivity of the curved printed circuit board is ≥95%. After heating and curing, the silver paste will not be squeezed out, and can be used for filling holes of curved substrates and substrates with poor high temperature resistance, ensuring that the circuit board has good electrical properties.

[0064] Typically but not limiting, the boiling point of the first solvent is 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C or any two of the ranges consisting of one or more ester solvents and ketone solvents; the boiling point of the second solvent is 60°C, 80°C, 100°C, 120°C, 140°C, 160°C or any two of the ranges consisting of one or more ether solvents and amide solvents; the volume ratio of the first solvent to the second solvent is 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any two of the ranges consisting of one or more ether solvents and amide solvents.

[0065] Typically but not limiting, the solid-containing regulating agent includes one or more esters and ketones having a saturated vapor pressure of 3 mmHg@20°C, 5 mmHg@20°C, 7 mmHg@20°C, 10 mmHg@20°C, 15 mmHg@20°C, 20 mmHg@20°C, 30 mmHg@20°C, 40 mmHg@20°C, 50 mmHg@20°C, 60 mmHg@20°C, 70 mmHg@20°C, 80 mmHg@20°C, 90 mmHg@20°C, 100 mmHg@20°C or a range consisting of any two of them, and the weight percentage of the solid-containing regulating agent in the rough mixed silver paste is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of them.

[0066] Typically but not limiting, the weight ratio of spherical silver powder to flake silver powder is 1:0.33, 1:0.4, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or a range consisting of any two of them.

[0067] The physical elimination treatment methods include one or more of vacuum homogenization, heating evaporation, vacuum rotary evaporation and vacuum drying.

[0068] Typically but not limiting, the number of cycles of vacuum homogenization is 2, 3, 4, 5, 6, 7, 8 times or a range consisting of any two of them, the vacuum degree of a single cycle is 2 kPa, 3 kPa, 4 kPa, 5 kPa, 6 kPa, 7 kPa, 8 kPa, 9 kPa, 10 kPa or a range consisting of any two of them, the rotation speed is 1000 rpm, 1200 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1800 rpm, 2000 rpm or a range consisting of any two of them, and the time is 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or a range consisting of any two of them.

[0069] Typically but not limiting, the heating evaporation temperature is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two of them, and the time is 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or a range consisting of any two of them.

[0070] Typically but not limitatively, the vacuum degree of the vacuum rotary evaporation is 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, 100Pa, 110Pa, 120Pa, 130Pa, 140Pa, 150Pa or a range consisting of any two of them, the rotation speed is 80rpm, 90rpm, 100rpm, 110rpm, 120rpm or a range consisting of any two of them, the temperature is 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two of them, and the time is 20min, 30min, 40min, 50min, 60min or a range consisting of any two of them.

[0071] Typically but not limiting, the vacuum degree of vacuum drying is 0.05 atm, 0.06 atm, 0.07 atm, 0.08 atm, 0.09 atm, 0.1 atm or a range consisting of any two of them, the temperature is 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two of them, and the time is 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or a range consisting of any two of them.

[0072] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0073] Example 1

[0074] (1) In sample cup 1, weigh 12.58 g of spherical silver powder (D50: 500 nm) and 5.02 g of flake silver powder (D50: 10 μm) at a weight ratio of 62.9:25.1 (spherical silver powder: flake silver powder = 1:0.4), and disperse them evenly using a vortex machine;

[0075] (2) In sample cup 2, 1.8 g of alicyclic epoxy resin CY179 (viscosity 300 mPa·s, accounting for 73% of organic phase A) in which 1% (accounting for epoxy resin) curing agent CTI100 has been dissolved, 0.3 g of alcohol ester dodecahydrate (boiling point 249°C), 0.3 g of ethylene glycol monomethyl ether (boiling point 124°C), and 0.06 g (accounting for 0.3% of conductive silver paste) of silver powder dispersing agent AKN01 are weighed at a weight ratio of 9:1.5:1.5 to obtain organic phase A;

[0076] (3) Add 0.7059 g of cyclohexanone (accounting for 3.5% of the coarse mixed silver paste A) (saturated vapor pressure 3.75 mmHg @ 20 °C) as a solid content regulator to the organic phase A, and use a homogenizer at 2000 rpm for 5 min to fully disperse the mixture to obtain an organic phase B;

[0077] (4) The silver powder in the sample cup 1 was evenly divided into three batches and added to the organic phase B. After each batch of silver powder was added, it was dispersed using a homogenizer at 800 rpm for 3 min to obtain a coarse mixed silver paste A. At this time, the organic phase accounted for 15% of the total weight of the silver paste, and the solid content of the silver paste was about 85%;

[0078] (5) Place the coarse mixed silver paste A into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -10°C, homogenize at 1500 rpm for 3 min, then homogenize at 400 rpm for 3 min as one cycle, and repeat 3 cycles in total to obtain a coarse mixed silver paste B;

[0079] (6) After the coarse mixed silver paste B returns to room temperature, it is dispersed using a three-roll mill to obtain a fine mixed silver paste C;

[0080] (7) The finely mixed silver paste C was placed in a homogenizer, and the vacuum degree was set to 5 kPa. The vacuum homogenization was performed at 1600 rpm for 5 min as one cycle, and the cycle was repeated 4 times in total to remove 0.7059 g of cyclohexanone from the finely mixed silver paste C to obtain a finely mixed silver paste D. At this time, the organic phase accounted for 12% of the total weight of the silver paste, and the solid content of the silver paste was increased from 85% to 88%;

[0081] (8) Place the finely mixed silver paste D into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -10°C, homogenize at 1500 rpm for 3 min, then homogenize at 400 rpm for 3 min as one cycle, repeat 3 cycles in total to obtain a conductive silver paste.

[0082] The conductive silver paste is as follows Figure 1As shown, the morphology after filling and curing is as follows Figure 2 shown.

[0083] Example 2

[0084] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a vacuum oven, the temperature is set to 60° C., and the vacuum degree is 0.1 atm and then kept warm for 60 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0085] Example 3

[0086] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a rotary evaporator, the vacuum degree is set to 100 Pa, the rotation speed is 100 rpm, the temperature is 60° C., and the rotary evaporation is performed for 30 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0087] Example 4

[0088] The difference from Example 1 is that in step (7), the fine mixed silver paste C is fixed on a hot plate, the temperature is set to 80° C., and the evaporation is carried out for 60 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0089] Example 5

[0090] The difference from Example 1 is that in step (1), 8.8 g of spherical silver powder and 8.8 g of flaky silver powder are weighed in a sample cup 1 at a weight ratio of 1:1 and dispersed evenly using a vortex instrument.

[0091] The conductive silver paste is as follows Figure 3 As shown, the morphology after filling and curing is as follows Figure 4 shown.

[0092] Example 6

[0093] The difference from Example 1 is that in step (1), 5.0 g of spherical silver powder and 12.6 g of flaky silver powder are weighed in a sample cup 1 at a weight ratio of 1:2.5, and are evenly dispersed using a vortex instrument.

[0094] Example 7

[0095] The difference from Example 1 is that in step (2), 1.8 g of alicyclic epoxy resin TTA26 (viscosity 600 mPa·s) in which 1% (based on epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of alcohol ester dodecahydrate, 0.3 g of ethylene glycol monomethyl ether, and 0.06 g of silver powder dispersing aid AKN01 are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2 to obtain an organic phase A.

[0096] Example 8

[0097] The difference from Example 1 is that in step (2), 1.8 g of a mixed resin (alicyclic epoxy resin CY179 (viscosity 300 mPa·s): bisphenol F type epoxy resin F170 (viscosity 2000 mPa·s) = 3:1) in which 1% (of epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of alcohol ester dodecahydrate, and 0.3 g of ethylene glycol monomethyl ether are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2, and 0.06 g of silver powder dispersing aid AKN01 are weighed at the same time to obtain an organic phase A.

[0098] The conductive silver paste is as follows Figure 5 As shown, the morphology after filling and curing is as follows Figure 6 shown.

[0099] Example 9

[0100] The difference from Example 1 is that in step (2), 1.8 g of alicyclic epoxy resin CY179 in which 1% (based on epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of DBE (boiling range 195-228° C.), 0.3 g of ethylene glycol monomethyl ether, and 0.06 g of silver powder dispersing agent AKN01 are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2 to obtain an organic phase A;

[0101] In step (3), 0.7059 g of methyl 2-methoxypropionate (saturated vapor pressure 7.5 mmHg @ 20°C) was added to the organic phase A, and the mixture was fully dispersed by homogenizing at 2000 rpm for 5 min to obtain an organic phase B.

[0102] Example 10

[0103] The difference from Example 1 is that in step (2), 1.8 g of alicyclic epoxy resin CY179 in which 1% (based on epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of DBE (boiling range 195-228° C.), 0.3 g of N,N-dimethylformamide (boiling point 153° C.), and 0.06 g of silver powder dispersing agent AKN01 are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2 to obtain an organic phase A;

[0104] In step (3), 0.7059 g of cyclohexanone was added to the organic phase A, and the mixture was homogenized at 2000 rpm for 5 min to obtain an organic phase B.

[0105] Embodiment 11

[0106] The difference from Example 1 is that in step (2), 1.8 g of alicyclic epoxy resin CY179 in which 1% (based on epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of ethylene glycol diacetate (boiling point 190.90° C.), 0.3 g of diethylene glycol dimethyl ether (boiling point 160° C.), and 0.06 g of silver powder dispersing agent AKN01 are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2 to obtain an organic phase A;

[0107] In step (3), 0.7059 g of cyclohexanone was added to the organic phase A, and the mixture was homogenized at 2000 rpm for 5 min to obtain an organic phase B.

[0108] The conductive silver paste is as follows Figure 7 As shown, the morphology after filling and curing is as follows Figure 8 shown.

[0109] Example 12

[0110] The difference from Example 1 is that in step (2), 1.8 g of alicyclic epoxy resin CY179 in which 1% (based on epoxy resin) of curing agent CTI100 is dissolved, 0.3 g of isophorone (boiling point 215.30° C.), 0.3 g of ethylene glycol monomethyl ether, and 0.06 g of silver powder dispersing aid AKN01 are weighed in a weight ratio of 9:1.5:1.5 in a sample cup 2 to obtain an organic phase A;

[0111] In step (3), 0.7059 g of ethyl acetate (saturated vapor pressure 75 mmHg @ 20°C) was added to the organic phase A, and the mixture was homogenized at 2000 rpm for 5 min to obtain an organic phase B.

[0112] Embodiment 13

[0113] The difference from Example 1 is:

[0114] In step (3), the solid content regulator cyclohexanone (accounting for 3% of the coarse mixed silver slurry A) is added to the organic phase A, and the mixture is fully dispersed using a homogenizer at 2000 rpm for 5 minutes to obtain an organic phase B;

[0115] In step (7), the fine mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 3 kPa, and the vacuum homogenization is performed at 1200 rpm for 5 minutes as one cycle, and a total of 3 cycles are performed to remove the solid-containing regulating agent cyclohexanone in the fine mixed silver paste C, thereby obtaining a fine mixed silver paste D.

[0116] Embodiment 14

[0117] The difference from Example 1 is:

[0118] In step (3), the solid content regulator cyclohexanone (accounting for 6% of the coarse mixed silver slurry A) is added to the organic phase A, and the mixture is fully dispersed using a homogenizer at 2000 rpm for 5 minutes to obtain an organic phase B;

[0119] In step (7), the fine mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 6 kPa, and the vacuum homogenization is performed at 1800 rpm for 3 minutes as one cycle, and a total of 5 cycles are performed to remove the solid-containing regulating agent cyclohexanone in the fine mixed silver paste C, thereby obtaining a fine mixed silver paste D.

[0120] Embodiment 15

[0121] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 2 kPa, and the vacuum homogenization is performed at 1000 rpm for 10 min as one cycle, and a total of 2 cycles are performed to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C to obtain a fine mixed silver paste D.

[0122] Example 16

[0123] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 10 kPa, and the vacuum homogenization is performed at 2000 rpm for 3 min as one cycle, and a total of 8 cycles are performed to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C to obtain a fine mixed silver paste D.

[0124] Embodiment 17

[0125] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a vacuum oven, the temperature is set to 40° C., the vacuum degree is evacuated to 0.05 atm and then kept warm for 90 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0126] Embodiment 18

[0127] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a vacuum oven, the temperature is set to 80° C., and the vacuum degree is 0.1 atm and then kept warm for 30 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0128] Embodiment 19

[0129] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a rotary evaporator, the vacuum degree is set to 50 Pa, the rotation speed is 80 rpm, the temperature is 40° C., and the rotary evaporation is performed for 60 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0130] Embodiment 20

[0131] The difference from Example 1 is that in step (7), the fine mixed silver paste C is placed in a rotary evaporator, the vacuum degree is set to 150 Pa, the rotation speed is 120 rpm, the temperature is 80° C., and the rotary evaporation is performed for 20 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0132] Embodiment 21

[0133] The difference from Example 1 is that in step (7), the fine mixed silver paste C is fixed on a hot plate, the temperature is set to 50° C., and the evaporation is carried out for 90 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0134] Embodiment 22

[0135] The difference from Example 1 is that in step (7), the fine mixed silver paste C is fixed on a hot plate, the temperature is set to 80° C., and the evaporation is carried out for 30 minutes to remove 0.7059 g of cyclohexanone in the fine mixed silver paste C.

[0136] Embodiment 23

[0137] (1) In sample cup 1, weigh 12.03 g of spherical silver powder (D50: 100 nm) and 4.01 g of flake silver powder (D50: 3 μm) at a weight ratio of 1:0.33 and disperse them evenly using a vortex machine;

[0138] (2) In sample cup 2, weigh 1.8 g of alicyclic epoxy resin CY179 in which 0.5% (in terms of epoxy resin) curing agent TC3632 has been dissolved, 0.4 g of diethylene glycol butyl ether acetate, and 0.2 g of allyl butyl ether, and weigh and add silver powder dispersing agent AKN210 (so that it accounts for 0.2% of the conductive silver paste) to obtain an organic phase A;

[0139] (3) adding butyl acetate (accounting for 2% of the coarse mixed silver paste A) as a solid content regulator to the organic phase A, and using a homogenizer at 1500 rpm for 10 min to fully disperse the mixture to obtain an organic phase B;

[0140] (4) The silver powder in the sample cup 1 was evenly divided into three batches and added to the organic phase B. After each batch of silver powder was added, it was dispersed using a homogenizer at 500 rpm for 5 min to obtain a coarse mixed silver paste A. At this time, the organic phase accounted for 15% of the total weight of the silver paste, and the solid content of the silver paste was about 85%;

[0141] (5) Place the coarse mixed silver paste A into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -15°C, homogenize at 1000 rpm for 10 min, then homogenize at 300 rpm for 10 min as one cycle, and cycle twice in total to obtain a coarse mixed silver paste B;

[0142] (6) After the coarse mixed silver paste B returns to room temperature, it is dispersed using a three-roll mill to obtain a fine mixed silver paste C;

[0143] (7) Place the fine mixed silver paste C in a homogenizer, set the vacuum degree to 5 kPa, and perform vacuum homogenization at 1600 rpm for 5 min as one cycle, and perform a total of 3 cycles to remove the solid-containing regulator in the fine mixed silver paste C to obtain a fine mixed silver paste D;

[0144] (8) Place the finely mixed silver paste D into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -15°C, homogenize at 1000 rpm for 10 min, then homogenize at 300 rpm for 10 min as one cycle, repeat 2 cycles in total, and obtain a conductive silver paste.

[0145] Embodiment 24

[0146] (1) In sample cup 1, weigh 5.4 g of spherical silver powder (D50: 2 μm) and 16.2 g of flake silver powder (D50: 20 μm) in a weight ratio of 1:3 and disperse them evenly using a vortex machine;

[0147] (2) In sample cup 2, weigh 1.8 g of alicyclic epoxy resin CY179 in which 1.5% (accounting for epoxy resin) of curing agent CTI80P has been dissolved, 0.24 g of 1,3-cyclohexanedione, and 0.36 g of N-methylpyrrole, and weigh and add silver powder dispersing agent KMT-J4201 (accounting for 1% of the conductive silver paste) to obtain organic phase A;

[0148] (3) adding butyl acetate (accounting for 10% of the coarse mixed silver paste A) as a solid content regulator to the organic phase A, and using a homogenizer at 2500 rpm for 3 min to fully disperse the mixture, thereby obtaining an organic phase B;

[0149] (4) The silver powder in the sample cup 1 was evenly divided into three batches and added to the organic phase B. After each batch of silver powder was added, it was dispersed using a homogenizer at 1000 rpm for 1 min to obtain a coarse mixed silver paste A. At this time, the organic phase accounted for 20% of the total weight of the silver paste, and the solid content of the silver paste was about 80%;

[0150] (5) Place the crude mixed silver paste A into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -5°C, homogenize at 2000 rpm for 2 min, then homogenize at 600 rpm for 2 min as one cycle, and repeat 10 cycles in total to obtain a crude mixed silver paste B;

[0151] (6) After the coarse mixed silver paste B returns to room temperature, it is dispersed using a three-roll mill to obtain a fine mixed silver paste C;

[0152] (7) Place the fine mixed silver paste C in a homogenizer, set the vacuum degree to 5 kPa, and perform vacuum homogenization at 1600 rpm for 5 min as one cycle, and perform a total of 8 cycles to remove the solid-containing regulator in the fine mixed silver paste C to obtain a fine mixed silver paste D;

[0153] (8) Place the finely mixed silver paste D into a refrigerated high-speed homogenizer NP-100, set the parameters to a temperature of -5°C, homogenize at 2000 rpm for 2 min, then homogenize at 600 rpm for 2 min as one cycle, and repeat 10 cycles in total to obtain a conductive silver paste.

[0154] Comparative Example 1

[0155] The difference from Example 1 is that step (3) and step (7) are not performed.

[0156] The silver paste is in the state of Fig. 9 As shown, the morphology after filling and curing is as follows Fig.10 shown.

[0157] Comparative Example 2

[0158] The difference from Example 1 is that step (7) is as follows: the finely mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 1 kPa, and the vacuum homogenization is performed at 1600 rpm for 5 minutes as one cycle, and a total of 3 cycles are performed.

[0159] The morphology of the silver paste after filling and curing is as follows Fig.11 shown.

[0160] Comparative Example 3

[0161] The difference from Example 1 is that step (7) is as follows: the finely mixed silver paste C is placed in a homogenizer, the vacuum degree is set to 20 kPa, and the vacuum homogenization is performed at 1600 rpm for 5 minutes as one cycle, and a total of 10 cycles are performed.

[0162] Comparative Example 4

[0163] The difference from Example 1 is that step (1) is as follows: 17.6 g of spherical silver powder is weighed in a sample cup 1 and dispersed evenly using a vortex instrument.

[0164] The silver paste is in the state of Fig.12 As shown, the morphology after the silver paste is filled and solidified is as follows Fig.13 shown.

[0165] Comparative Example 5

[0166] The difference from Example 1 is that step (1) is as follows: 17.6 g of flaky silver powder is weighed in a sample cup 1 and dispersed evenly using a vortex instrument.

[0167] Comparative Example 6

[0168] The difference from Example 1 is that step (2) is as follows: in a sample cup 2, 1.8 g of epoxy resin E51 (viscosity 15000 mPa·s), 0.3 g of alcohol ester dodecahydrate, 0.3 g of ethylene glycol monomethyl ether, and 0.06 g of silver powder dispersing aid AKN01 are weighed at a weight ratio of 9:1.5:1.5 to obtain an organic phase A.

[0169] The silver paste is in the state of Fig.14 As shown, the morphology after the silver paste is filled and solidified is as follows Fig.15 shown.

[0170] Comparative Example 7

[0171] The difference from Example 1 is that

[0172] Step (2) is: in a sample cup 2, 1.8 g of alicyclic epoxy resin CY179, 0.3 g of alcohol ester dodecahydrate, 0.3 g of ethylene glycol monomethyl ether and 0.06 g of silver powder dispersing agent AKN01 are weighed at a weight ratio of 9:1.5:1.5 to obtain an organic phase A;

[0173] Step (3) is: adding 0.7059 g of acetone (saturated vapor pressure 185.25 mmHg @ 20°C) to the organic phase A, and using a homogenizer at 2000 rpm for 5 minutes to fully disperse the mixture, to obtain an organic phase B.

[0174] Prepare silver paste as Fig.16 As shown, the morphology after the silver paste is filled and solidified is as follows Fig.17 shown.

[0175] The silver pastes prepared in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0176] Performance Test:

[0177] 1. Printing continuous discharge time: The prepared silver paste is placed in a 3cc material tube, homogenized at 1500rpm for 5min, and then centrifuged at 2000rpm for defoaming for 2min to obtain a uniform, bubble-free silver paste. A steel needle with an inner diameter of 500μm is installed at the discharge port of the material tube, and then the material tube is fixed to the booster pen, the air pressure is set to 5psi, the air outlet valve is opened to start discharging and timing until the needle is completely blocked and unable to discharge. In addition, after a lot of verification, according to the above parameters, the silver paste in the 3cc material tube is almost completely discharged after 24h of discharging. It can be considered that the silver paste can be discharged stably for a long time during the printing process for more than 24h without clogging the needle to meet the needs of mass production. Therefore, the standard for judging whether the silver paste can be discharged stably for a long time is set to a printing continuous discharge time of ≥24h. During this period, the discharge flow fluctuation is monitored by the change in the quality of the silver paste. It is believed that the discharge flow fluctuation does not exceed 10%, which can meet the long-term stable printing requirements of the process.

[0178] 2. Conductivity test after hole filling and curing: Put the prepared silver paste in a 3cc material tube, homogenize it at 1500rpm for 5min, and then use a centrifuge at 2000rpm to defoam for 2min to obtain a uniform, bubble-free silver paste. Install a steel needle with an inner diameter of 200μm at the outlet of the material tube, and then fix the material tube to the booster pen, set the air pressure to 40psi, and use a 3D printing device (self-developed) to perform a hole filling test on a curved porous epoxy glass fiber board with a curvature of 30. The hole diameter is 500μm and the hole depth is 1mm. After the hole filling is completed, use an oven at 100℃ to cure for 30min, observe the morphology of the silver paste in the hole after grinding, and use a multimeter to test the conductivity after hole filling. If the resistance value is ≤0.1Ω, it is judged to be conductive, and the number of conductive holes is recorded as x. The conductivity C=(x×100%) / 100 is converted. If the conductivity is ≥95%, it is qualified.

[0179] Table 1

[0180]

[0181]

[0182] From the data in the table we can see that:

[0183] Compared with Comparative Example 1, the discharge performance and the conductive performance after hole filling of the high solid silver paste prepared in Examples 1, 2, 3, and 4 are better than those prepared directly by the common process. Figure 1 and Fig. 9 It can be seen that the high-solid silver paste prepared by Example 1 using the method of the present invention is uniform in state and has a smooth surface, while the high-solid silver paste directly prepared by Comparative Example 1 using the conventional process has a rough surface and is obviously unevenly dispersed. Figure 2 and Fig.10 It can be seen that the high-solid silver paste prepared in Example 1 of the present invention has a dense and uniform morphology without holes after curing, while the high-solid silver paste prepared in Comparative Example 1 of the conventional process has a large number of agglomerates and holes and a poor morphology. Therefore, the uniformity of the high-solid silver paste prepared by the process of the present invention is significantly better than that of the high-solid silver paste prepared by the conventional process.

[0184] Compared with Comparative Examples 2 and 3, the discharge performance and conductivity of the silver paste prepared in Example 1 according to the vacuum degree, time, and cycle number parameters selected by the present invention are significantly better than the silver paste prepared in Comparative Examples 2 and 3 with low vacuum degree and excessive cycle time. Figure 2 and Fig.11 It can be seen that the silver paste prepared in Example 1 has a dense and uniform hole-filling morphology without agglomeration, while the silver paste prepared in Comparative Example 1 has a poor hole-filling morphology with a small amount of pores and silver agglomerations.

[0185] Compared with Comparative Examples 4 and 5, the silver paste prepared by Examples 5 and 6 using a combination of spherical silver powder and flaky silver powder as conductive fillers has better discharge performance and conductivity than the silver paste prepared by using only a single morphology silver powder. Figure 3 and Fig.12 It can be seen that the high solid silver paste prepared by the process of the present invention has better dispersibility and is more uniform. Figure 4 and Fig.13 It can be seen that the silver pastes of Example 5 and Comparative Example 4 are relatively dense after filling the holes macroscopically, but Comparative Example 4 only uses spherical silver powder and has fewer conductive paths, so it cannot conduct electricity after curing at 100°C.

[0186] The discharge performance and conductive performance of the silver paste obtained in Comparative Example 6 are similar to those in Examples 7 and 8. Figure 6 and Fig.15 It can be seen that the silver paste prepared by using the high-viscosity E51 resin in Comparative Example 6 will be squeezed out after curing, resulting in protrusion on the top of the substrate and hollowness on the bottom; while the high-solid silver paste prepared by using the low-viscosity alicyclic epoxy resins CY179 and TTA26 in Examples 7 and 8 is dense and uniform after curing and will not be squeezed out.

[0187] Compared with Comparative Example 7, the conductivity and discharge performance of the high solid silver paste prepared by using the solid content regulator selected in Examples 9, 10, 11, and 12 are better than the high solid silver paste prepared by using acetone (saturated vapor pressure of 185.25 mmHg@20°C) as the solid content regulator. Figure 7 and Fig.16 It can be seen that there is a significant difference between the silver paste state of Example 11 and Comparative Example 7. The silver paste of Comparative Example 7 has a rough surface and poor dispersibility. Figure 8 and Fig.17 It can be seen that the silver paste of Example 11 has a dense and uniform morphology after curing, while the silver paste of Comparative Example 7 has a large number of holes and agglomerated silver blocks after curing.

[0188] It can be seen from the above that, compared with the comparative example, each embodiment of the present invention first prepares a coarse mixed silver paste with a low silver powder solid content, so that the silver powder is fully and evenly dispersed in the organic phase, and then removes the excess volatile solid content regulator in the silver paste by physical elimination treatment, so as to increase the silver powder solid content in the silver paste. The present invention uses esters and ketones with specific saturated vapor pressure as solid content regulators, which can be conveniently removed by physical elimination while adjusting the solid content of the silver paste, so that the prepared conductive silver paste still has good dispersibility at high solid content. The present invention improves the dispersion uniformity of the silver paste through a two-step solid content regulation method, so that the silver paste can be completely cured at a lower temperature and still have a certain conductivity. After curing, it is dense and full, and there are no holes or cracks in the morphology.

Claims

1. A conductive hole-filling silver paste, characterized in that: The conductive hole-filling silver paste is used for printing hole-filling with a line width of 500 μm or less. During the continuous 24-hour discharge process of the conductive hole-filling silver paste, the flow fluctuation is less than 10%. The preparation method of the conductive hole-filling silver paste comprises the following steps: Step S1, mixing epoxy resin, curing agent, a first solvent and a second solvent to obtain an organic phase; Step S2, adding a solid-containing regulator to the organic phase, and performing a first homogenization dispersion to obtain a modified organic phase; Step S3, adding silver powder to the modified organic phase, and performing a second homogenization dispersion to obtain a coarse mixed silver slurry; Step S4, performing physical elimination treatment on the coarse mixed silver paste to remove the solid-containing regulator to obtain the conductive hole-filling silver paste; Wherein, the viscosity of the epoxy resin is ≤1000mPa·s; The solid content regulator includes one or more of ethyl acetate, propylene glycol methyl ether acetate, n-propyl acetate, sec-butyl acetate, methyl 2-methoxypropionate, tert-butyl propionate, butyl acetate, cyclohexanone, 3,3-dimethoxy-2-butanone, cyclopentanone, 2-hexanone and methyl isobutyl ketone, and the weight percentage of the solid content regulator in the coarse mixed silver paste is 2-10%; The silver powder includes spherical silver powder and flaky silver powder, the D50 of the spherical silver powder is 100nm~2μm, the D50 of the flaky silver powder is 3~20μm, and the weight ratio of the spherical silver powder to the flaky silver powder is 1:(0.33~3); The solid content of the coarsely mixed silver paste is 80-85%, and the solid content of the conductive hole-filling silver paste is 87-92%. The first solvent is one or more ester solvents and ketone solvents with a boiling point of 180-300° C., the second solvent is one or more organic solvents with a boiling point of 60-160° C., and the volume ratio of the first solvent to the second solvent is 1:(0.5-1.5).

2. The conductive hole-filling silver paste according to claim 1, characterized in that: In step S4, the physical elimination treatment method includes one or more of vacuum homogenization, heating evaporation, vacuum rotary evaporation and vacuum drying; The vacuum homogenization cycle number is 2 to 8 times, the vacuum degree of a single cycle is 2 to 10 kPa, the rotation speed is 1000 to 2000 rpm, and the time is 3 to 10 min; and / or The heating evaporation temperature is 50-80°C and the time is 30-90 minutes; and / or The vacuum degree of the vacuum rotary evaporation is 50-150 Pa, the rotation speed is 80-120 rpm, the temperature is 40-80° C., and the time is 20-60 min; and / or The vacuum degree of the vacuum drying is 0.05-0.1 atm, the temperature is 40-80° C., and the time is 30-90 min.

3. The conductive hole-filling silver paste according to claim 1, characterized in that: The first solvent includes one or more of DBE, ethylene glycol diacetate, alcohol ester dodecahydrate, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, di-tert-butyl malonate, ethyl succinate, isophorone, 1,3-cyclohexanedione, 4-ethylcyclohexanone and 1,2-cyclohexanedione; The second solvent includes one or more of ethylene glycol monomethyl ether, diethylene glycol dimethyl ether, allyl butyl ether, 1,1,3,3-tetramethoxy-1,3-dimethyldisiloxane, ethylene glycol ethyl ether, propylene glycol dimethyl ether, ethylene glycol dimethyl ether, N,N-dimethylformamide, 1-methyl-3-pyrrolidone, N-methylpyrrole and 1,1-dimethoxy-N,N-dimethylethylamine.

4. The conductive hole-filling silver paste according to claim 1 or 2, characterized in that: In the step S1, The epoxy resin comprises bisphenol F epoxy resin and / or alicyclic epoxy resin, wherein the weight percentage of bisphenol F epoxy resin in the epoxy resin is ≤30%; and / or The weight percentage of the epoxy resin in the organic phase is 60-90%; and / or The curing agent is a cationic epoxy resin curing agent; and / or the weight ratio of the epoxy resin to the curing agent is 100:(0.5~1.5).

5. The conductive hole-filling silver paste according to claim 1 or 2, characterized in that: The step S1 also includes the step of adding a dispersing aid during the mixing process; The weight percentage of the dispersing aid in the conductive hole-filling silver paste is 0.2-1%.

6. The conductive hole-filling silver paste according to claim 1 or 2, characterized in that: The first homogenate dispersion is performed at a rotation speed of 1500-2500 rpm for 3-10 min; and / or the second homogenate dispersion is performed at a rotation speed of 500-1000 rpm for 3-15 min.

7. The conductive hole-filling silver paste according to claim 1 or 2, characterized in that: The step S4 comprises the following steps: Step S41, subjecting the coarse mixed silver paste to a first freezing homogenization and a rolling dispersion in sequence to obtain a first fine mixed silver paste, wherein the temperature of the first freezing homogenization is -15 to 0°C; Step S42, performing the physical elimination treatment on the first fine mixed silver paste to obtain a second fine mixed silver paste; Step S43, subjecting the second finely mixed silver paste to a second freezing homogenization to obtain the conductive hole-filling silver paste, wherein the temperature of the second freezing homogenization is -15 to 0°C.

8. A curved printed circuit board, characterized in that: The curved printed circuit board is obtained by filling holes with the conductive silver paste according to any one of claims 1 to 7, the resistance of the filled holes of the curved printed circuit board is ≤0.1Ω, and the conductivity of the curved printed circuit board is ≥95%.

Citation Information

Patent Citations

  • Environment-friendly low-resistance low-temperature conductive silver paste and preparation method thereof

    CN113096848A

  • Method for preparing silver paste used for back electrode of photovoltaic cell

    CN102360628A

  • Primer composition and its preparing process and use

    CN1986708A

Cited By

  • Method for manufacturing fan-out type packaging rewiring layer of integrated circuit chip

    CN120497202A